2021
DOI: 10.3390/ma14051259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg on the Formation of Periodic Layered Structure during Double Batch Hot Dip Process in Zn-Al Bath

Abstract: The article presents the results of studies on the influence of Mg on the formation of the periodic layered structure of the Zn-AlMg coatings. These coatings were produced by the double batch hot dip method in a Zn bath and then in a Zn-Al(Mg) bath with a content of 15, 23, 31 wt.% Al and 3, 6 wt.% Mg. The microstructure of the coatings (OM, SEM) was revealed and the phase composition (XRD) obtained in two-component Zn-Al baths and Zn-AlMg baths were determined. The periodic layered structure was found to cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The formation of the coatings in the two-component ZnAl23 bath leads to the formation of a periodic layered structure, which causes the formation of porous coatings of excessive thickness. The addition of Mg to the bath reduces this phenomenon, but does not eliminate it completely [11]. The research shows that the addition of Si to the bath helps to inhibit the formation of a periodic layered structure.…”
Section: Mgmentioning
confidence: 88%
See 1 more Smart Citation
“…The formation of the coatings in the two-component ZnAl23 bath leads to the formation of a periodic layered structure, which causes the formation of porous coatings of excessive thickness. The addition of Mg to the bath reduces this phenomenon, but does not eliminate it completely [11]. The research shows that the addition of Si to the bath helps to inhibit the formation of a periodic layered structure.…”
Section: Mgmentioning
confidence: 88%
“…The growth of the coating under such conditions also causes the formation of a periodical layered structure (PLS), characterizing the alternating structure of the intermetallic phases layers of the FeAl system and the alloy layers of the metalizing bath. A slight decrease in the reactivity of steel is caused by the addition of Mg to the bath [11]. On the other hand, the coatings obtained in ZnAl baths containing Mg show very good corrosion resistance [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on the MgZn 2 phase within Zn-Al-Mg coatings, considered a crucial factor in enhancing these coatings’ corrosion resistance [ 3 , 12 , 13 ]. However, as research progresses, some studies have also identified the presence of the Mg 2 Zn 11 phase, indicating that the phase composition of these coatings is more complex than expected [ 8 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%